Perancangan Bilah Turbin Angin Tipe Inverse Taper Naca 4412 - Putra, Adipa; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The condition of electricity in Pekanbaru is really apprehensive, there are still many people who have not been supplied with electricity around the area. Wind energy as a renewable energy source has great potential to overcome the problem of electricity dependence. The relatively low wind speed conditions can be used efficiently by designing blades that are suitable for the wind speed in Pekanbaru area. The blades are designed using aerodynamic equations with software such as Q-Blade and Microsoft excel to determine blade geometry, as well as Autodesk Inventor 2013 to perform blade modeling. As a result, the blade that is designed has a tough structure and can produce mechanical power at low wind speeds with a blade radius of 1.3 m and a root chord length of 0.17 m and a chord length at the end of 0.34 m with a torsion angle at the base is 23.9 Â° and the torsion angle is 7.3 Â° at the ends of the blade. Keywords: Blades, Chords,Inverse Taper, Wind Turbines.